Duolingo Application and Vocabulary Scores of Seventh Graders: Pencapaian Aplikasi Duolingo dan Skor Kosakata Siswa Kelas 7 - Hyan Siswanto; Yuli Astutik (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Vocabulary mastery is a fundamental component of English language learning, particularly at the junior high school level where lexical knowledge supports broader communicative competence. Specific Background In Indonesian secondary classrooms, vocabulary instruction often relies on rote memorization and textbook-centered methods that may limit engagement and retention. Digital platforms such as Duolingo offer gamified and interactive learning environments aligned with Mobile-Assisted Language Learning practices. Knowledge Gap Despite its global popularity, systematic classroom-based evidence regarding Duolingo integration in Indonesian junior high schools remains limited. Aims This study aims to examine whether the use of the Duolingo application is associated with differences in vocabulary mastery among seventh-grade students at SMP Muhammadiyah 8 Tanggulangin. Results Using a pre-experimental one-group pre-test and post-test design with 23 students, the findings indicate an increase in mean scores from 55.87 to 82.61, with paired-sample t-test results showing statistical significance (p = 0.000). Novelty The study provides empirical evidence from a local Indonesian junior high school context regarding structured Duolingo classroom integration. Implications The findings suggest that gamified mobile applications can serve as complementary tools in formal English instruction, particularly for vocabulary practice, while highlighting the need for controlled designs and longer intervention periods in future research. Keywords: Duolingo Application, Vocabulary Mastery, Junior High School, Mobile-Assisted Language Learning, Gamified Learn Key Findings Highlights: Mean vocabulary scores increased by 26.74 points after classroom integration. Statistical testing confirmed significant pre-test and post-test differences. Structured mobile-based practice supported active classroom participation.